Coastal Community Perceptions of Conservation Areas in Sumalata District, North Gorontalo Regency - Pradilia, Andi Desiah; Saiful; Isima, Hartaty (Jurnal IPTEKS Pemanfaatan Sumberdaya Perikanan, 2024)
This research aims to analyze public perceptions regarding coastal conservation areas in Sumalata District, North Gorontalo Regency. Conservation areas have an important role in protecting marine ecosystems, but effective management requires the support of coastal communities. This research uses survey and interview methods to explore the community's understanding of the benefits, challenges and their role in managing conservation areas. The research results show that community attitudes towards area conservation are generally positive, with a good understanding of the importance of conservation. In addition, the public's awareness of marine conservation regulations is high, especially regarding the implementation of protection regulations which have a direct impact on their daily activities. This research recommends increasing education and active community involvement in the management of conservation areas as an effort to increase the effectiveness of marine conservation in Sumalata District, North Gorontalo Regency.